Evaluation of Acid Value, Free Fatty Acids, and Malondialdehyde (MDA) Content in Chevon Fat: A Pre- and Post-Roasting Comparison - M. S. Soenarno; M. Arifin; S. Prabowo; Salundik; D. Murtini; Q. Alifiya; R. R. S. Wihansah (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2024)
The roasting process using high heat will decrease the quality of fat and can produce toxic compounds that are mutagenic and carcinogenic to the body if consumed over a long period of time. This study aims to analyze the effect of roasting on chevon fat. The roasting process in this study was carried out using charcoal with a distance of 5 cm between the charcoal and the fat for 10 minutes. The observed test parameters were acid value, free fatty acids, and malondialdehyde (MDA) levels. The data obtained from the study were analyzed using a T-test based on the treatment of chevon fat before and after roasting. The results showed that the acid value and free fatty acid value of the fat after roasting were significantly (P<0.05) higher than before roasting, while the MDA value was not significantly different (P>0.05). This study indicates a change in the quality of chevon fat after roasting.